(untitled) (Global Journal of Management and Business Research, 2021)
Despite the huge literature that has been carried to investigate the determinants of the private equity market, studies examining the extent of the SQB in the private equity investments’ decisions are missing. Our regressions are based on a data set that covers 24 OECD members’ countries from 2007 to 2015. We discovered the absence of a link between the SQB and the choice of private equity investments. However, the added value by activity, the private equity country attractiveness index, and the research & development expenditures have a significant impact on the choice of the investment sector. Thus, private equity investors are considered rational decision-makers compared to individuals. The crucial role of the status quo has been shown in many fields. Nevertheless, whether this bias affects the private equity investment decision at the country level remains unanswered by prior research.